Ancient Egyptian Letters to the Dead : The Realm of the Dead through the Voice of the Living - Hsieh, Julia, (Harvard Egyptological Studies ;, 2022)
In Ancient Egyptian Letters to the Dead: the Realm of the Dead through the Voice of the Living Julia Hsieh investigates the beliefs and practices of communicating with the dead in ancient Egypt through close lexical semantic analysis of extant Letters. Hsieh shows how oral indicators, toponyms, and adverbs in these Letters signal a practice that was likely performed aloud in a tomb or necropolis, and how the senders of these Letters demonstrate a belief in the power and omniscience of their deceased relatives and enjoin them to fight malevolent entities and advocate on their behalf in the afterlife. These Letters reflect universals in beliefs and practices and how humankind, past and present, makes sense of existence beyond death.